Case report: Two clusters of Creutzfeldt–Jakob disease cases within 1 year in West Michigan - Rong, Ling Ling; Lannen, Nicholas J.; Tank, Evan C.; Feistel, Jessica L.; Therasse, Christopher J.; Potluri, Anvita; Khan, Muhib; Min, Jiangyong (Frontiers in Neurology, 2023)
Background: Creutzfeldt-Jakob disease (CJD) is a rare, rapidly progressive and uniformly fatal neurodegenerative disease. The reported incidence of CJD is 1 to 2 per million people worldwide annually, with fewer than 1,000 cases in the United States per year. Here we report a unique case series on temporo-spatial clusters of CJD cases in West Michigan. Methods: Five CJD cases consisting of 2 temporal clusters were seen from July 2021 to June 2022 at Corewell Health West hospitals. All patients had brain MRI, EEG, and CSF tests. Four patients underwent autopsies. Results: All patients’ MRI showed characteristic CJD patterns. Four patients had positive CJD panel in CSF. One patient had typical CJD EEG findings. Four patients were confirmed as sporadic CJD by autopsy. All patients died within 3 months after CJD was suspected. Discussion: All patients lived within a 90-mile radius of Grand Rapids, MI, and two lived in the same county. West Michigan has a population of 1.6 million people, and the four counties where five patients lived have a combined population of 395,104, indicating CJD new case rate 3.1 and 12.5 per million people, respectively. Corewell Health is one of the three major healthcare systems in West Michigan. The actual incidence of CJD in West Michigan is likely even higher. This dense temporal and spatial cluster of CJD cases poses a serious public health challenge and warrants urgent investigation.